Action mode of triazines and toxic effects on vertebrates - Severi-Aguiar, G. D.C.; Silva-Zacarin, E. C.M.; Campos-Pereira, F. D. [UNESP]; Alves, A. A. (My University, 2013)
Triazines are the family of herbicides that include atrazine, ametryn and simazine that are widely used in Brazil and can contaminate groundwater. Cattle can accumulate herbicides in their body through ingestion plants infested with these compounds and one of the ways, by which, human beings are exposed to atrazine is through cattle meat and milk consumption. The toxicity of these compounds can be explained mainly by their interaction with microsomal biotransformation processes. The herbicides per se or their metabolites or the secondary products of oxidative stress interact with biomolecules such proteins and DNA affecting a lot of cellular types. Cellular effects of chemicals might involve recruitment or de-repression of cell death mechanisms. Whether a cell survives or dies in the presence of a chemical insult is often determined by proliferative status, repair enzyme capacity, and the ability to induce proteins that either promote or inhibit the cell death process. In this chapter we will present an extensive bibliographical review about this herbicide class focusing its effects on vertebrates, looking for defense cellular mechanisms, at morphological and biochemical levels.